CUSTOMER SATISFACTION ANALYSIS REGARDING USING HALODOC APPLICATION CUSTOMER SATISFACTION INDEX (CSI) METHOD - Sari, Dely Indah; Harahap, Widya Lestari; Ali, Faishal (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: Halodoc is an ICT that supports access to health service facilities, with various facilities such as consultations with doctors, purchasing medicines, making appointments with hospitals, as well as several other health support facilities. This research is based on calculations using the Customer Satisfaction Index (CSI) method to determine the overall level of customer satisfaction with an approach that considers the level of importance of product or service attributes as measured by an importance scale (Importance), a satisfaction/performance level scale (Performance) and the question indicators include usability, information quality, interaction quality, then the satisfaction level criteria are obtained with a CSI value of 61.29%, meaning that the patient gives the criteria as being quite satisfied with Halodoc services. Keywords: CSI, halodoc, patient  Abstrak: Halodoc merupakan TIK yang mendukung akses fasilitas pelayanan kesehatan, dengan berbagai fasilitas yang dimiliki seperti konsultasi dengan dokter, pembelian obat, buat janji dengan rumah sakit, serta beberapa fasilitas pendukung kesehatan lainnya. Penelitian ini berdasarkan perhitungan menggunakan metode Customer Satisfaction Index (CSI) untuk menentukan tingkat kepuasan pelanggan secara menyeluruh dengan pendekatan yang mempertimbangkan tingkat kepentingan dari atribut-atribut produk atau jasa yang diukur dengan skala tingkat kepentingan (Importance), skala tingkat kepuasan/kinerja (Performance) dan indikator pertanyaan meliputi usability, information quality, interaction quality maka diperoleh kriteria tingkat kepuasan dengan nilai CSI 61.29% artinya bahwa pasien memberikan kriteria cukup puas terhadap layanan Halodoc. Kata kunci: CSI, halodoc, pasien